Optical Spectroscopy and Photoionization Model of Planetary Nebula NGC 6572 - Muhammad Fajrin; Hakim Luthfi Malasan; Evan Irawan Akbar (Journal of Mathematical and Fundamental Sciences, 2023)
We investigated NGC 6572 through optical spectroscopy to determine its kinematical and chemical properties. Two intermediate dispersion spectra (R~5000) centered around Hα and Hβ were used to derive the nebular expansion velocity from emission lines associated with Hα, Hβ, [OIII], [NII], and [SII] ions. A low dispersion spectrum (R~1000) was used to determine the nebular electron temperature, density, and chemical composition. We performed photoionization modeling to construct a self-consistent nebular model, while intermediate-resolution spectral images showed the global elliptical structure of the nebula. The expansion velocity deduced from most of the emission lines is consistent with the typical expansion velocity of planetary nebulae, i.e., around 15-20 kms-1. The nebular physical properties align well with those determined by other studies. The nebular abundances were found to be lower than the solar abundances (except for oxygen) but still comparable with the abundances derived by other researchers. The photoionization model generated spectral lines that are consistent with the lines found in the observations. Further spectroscopic observations with higher resolution and wider range at various position angles will be very useful to reveal a more complete and detailed structure of the nebula and to improve the determination of the nebular physical properties.